ESTIMATION OF RADIOMETRIC PERFORMANCE OF ELEKCTRO-OPTICAL IMAGING SENSOR OF LOW EARTH EQUATORIAL ORBIT LAPAN SATTELITE - Ahmad Maryanto; Andy Indradjad; Dinari Nikken Sirin; Ayom Widipaminto (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2012)
Study  of  spectro-radiometric  performance  of  electro-optical  imager  which  is planned  to  be  launched  on  low  earth  equatorial  orbit  LAPAN  satellite  was  conducted through  simulative  calculation  of  image  irradiance  and  its  associated  generated  voltage  at the image detector output. Simulative calculation was applied to three scenarios of selected spectral  bands.  Those  spectral  bands  were  selected  spectra  (1),  which  consisted  of  spectral bands  B = (390-540 and 790-900) nm,  G = (470-610 and 700-900 )  nm, and R = (590-650 and 650-900) nm; selected spectra (2) consisted  of B1 = (390-540) nm,  G1 = (470-610) nm, and  R1  =  (590-650)  nm;  and  selected  spectra  (3)  consisted  of  B1(Green)  =  (525-605)  nm, B2(Red) = (630-690) nm, and B3(NIR) = (750-900) nm, on three scenarios of optical aperture or f-number (N)  2.8, 4.0, and  5.6.  Green grasses, dry  grasses, and conifers  were examples of the imaged target, chosen as representation of vegetations. Kodak KLI-8023 was used as the  optical  detector.  The  integration  time  was  assumed  3  miliseconds  which  correspond  to about 20 m ground sampling distance (GSD). Solar zenith angle were varying from 90 (early morning)  to  0  (solar  noon).  The  results  showed  that  option  (3)  of  selected  spectra,  as proposed  for  pushbroom  imager  of  LAPAN  satellite,  was  relatively  accepted  to  be implemented  and  complemented  with  f-number  4.0  of  optical  system  used.  Whereas simulation RGB color displayed  composed by R = B2(Red), G = B3(NIR), B = B1(Green) also showed a greenish color sense as expected for vegetation imaged target.